PENGEMBANGAN HIGHER ORDER THINKING MULTIPLE CHOICE TEST UNTUK MENGUKUR KETERAMPILAN BERPIKIR KRITIS IPA KELAS VII SMP/MTs - Hartini, Hartini; Sukardjo, Sukardjo (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2015)
This study aims to: (1) develop higher order thinking multiple choice test (HOT-MCT) to measure the critical thinking skills of students of class VII IPA SMP/MTs, (2) determine the quality of the test theoretically, and (3) determine the quality of the test empirically. The procedure consists of seven-step, which adapted from 10 models of research and development steps Borg & Gall which includes: (1) the preliminary study, (2) planning , (3) development, (4) a small test group, (5) revision, (6) field trials, and (7) revision. The quality of the test theoretically validated by experts and science teachers. Empirically test the quality of trials conducted small groups and field trials. Analysis of the data using the parameters of the classical theory. This research resulted in about HOT-MCT with the following explanation: (1) a multiple choice question with four answer options consisting of 23 items was, (2) the test is valid theoretically valid, and (3)the test is valid emperically with reliability index Î± = 0.723.